MANAJEMEN KELAS DAN PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMPN 1 PAGADEN TAHUN AJARAN 2018-2019 - Harisuddin, Muhammad Iqbal (Jurnal Administrasi Pendidikan, 2020)
This research was conducted to find out whether the improvement in the ability to understand mathematical concepts of students in SMPN 1 Pagaden in the Academic Year 2018-2019 was higher using the Discovery Learning model when compared to those who obtained ordinary learning. The research method used a quasi-experimental pretest-posttest randomized control group research design. Population of all class VII students of SMPN 1 Pagaden Academic Year 2018-2019 with a sample of two classes purposively selected. The experimental group is class VII E, the learning model is Discovery Learning while the control group is class VII F, using the normal learning model. The instruments used in this study were in the form of tests and non-tests. The ability to understand students' mathematical concepts is measured by test instruments in the form of questions in the form of descriptions. Student responses are known by non-test instruments in the form of questionnaires. The results of the study increased the ability to understand the mathematical concepts higher in class VII students of SMPN 1 Pagaden Academic Year 2018-2019 with the Discovery Learning learning model rather than obtaining ordinary learning. The Discovery Learning learning model provides a positive response for class VII students of SMPN 1 Pagaden Academic Year 2018-2019.